The Use of the School-Environment-Based Educational Game 'Language Detective' to Improve Vocabulary and Spelling Mastery Among Phase B Elementary School Students at Nania Christian Elementary School - Rumaruson, Fica Agralce; Koeswanti, Henny Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Limited vocabulary mastery and spelling proficiency in Indonesian remain challenges for elementary school students, largely due to teaching methods that tend to be teacher-centered, thereby limiting active student engagement. This study aims to describe the use of the school-environment-based educational game "Detektif Bahasa" (Language Detective) as an instructional innovation designed to improve the vocabulary and spelling skills of Phase B elementary students at Nania Christian Elementary School. A qualitative descriptive approach was employed, with Phase B students at the school serving as the subjects. Data were collected through observation, documentation, and interviews during the implementation of the innovation. Data analysis involved the stages of data reduction, data presentation, and conclusion drawing. The results indicate that implementing the "Detektif Bahasa" educational game successfully shifted instruction from a teacher-centered model to a student-centered one by utilizing gamification and contextual, school-environment-based learning. Students assumed the role of "Language Detectives," exploring various written materials within the school environment to discover new vocabulary and identify spelling errors; they then collaboratively discussed their findings and displayed them on the classroom's "Literacy Tree." This innovation enhanced active participation, learning motivation, critical thinking skills, collaboration, vocabulary mastery, and the ability to apply Indonesian spelling rules in real-world contexts. Thus, the school-environment-based "Detektif Bahasa" educational game serves as an effective, innovative teaching strategy for strengthening the language literacy skills of elementary school students.